Pengaruh Variasi Berat Molekul Polietilen Glikol terhadap Sifat Mekanik Poliuretan - Eli Rohaeti; N M Surdia (Jurnal Matematika & Sains, 2003)
Synthesis of polyurethane was carried out by using diisocyanate monomer, (methylene-4,4â-diphenyldiisocyanate (MDI) and polyether monomer polyethylene glycol (PEG). The synthesis of polyurethane was undertaken by varying the molecular weight of PEG. The effect of molecular weight of PEG on the mechanical properties of polyurethane was observed. The variation of molecular weight of PEG was 200, 400, and 1000. Polymerization reaction was carried out at room temperature with a mol ratio of MDI to PEG was 1.17. The mechanical properties of polyurethane were characterized using AGS-500D Shimadzu tensile testing machine, with a cross head speed of 50 mm/minutes. The tensile test showed that increasing molecular weight of PEG used in the synthesis of polyurethane resulted in decreasing of the tensile strength at break of polyurethane, and increasing of elongation at break. The elasticity modulus was 92.21 kPa for polyurethane based on PEG 200; 8.96 kPa for polyurethane based on PEG 400; and 0.27 kPa for polyurethane based on PEG 1000.